Management of longstanding synovial sarcoma of the shoulder region – A case report. (June 2017) - Al-Busaidi, Said Saud; Al-Hashmi, Sheikhan Nasser; Jayachandran, Renjit Kumar
Abstract: Synovial sarcoma comprises approximately 8% of all soft tissue sarcomas. It occurs at all ages and it has a predilection for the extremities of young adults. We report here a patient who had synovial sarcoma over the shoulder joint and waited for six months before seeking any treatment. This patient was managed by a multidisciplinary team and discussed at a Tumour Board Meeting. She had neoadjuvant chemotherapy followed by tumour excision. Subsequently she had radiotherapy. The patient's upper limb was preserved and the function was not affected.